Prognostic value of the immediate response to surfactant. Issue 3 (November 1994) - Kuint, J; Reichman, B; Neumann, L; Shinwell, E S
Abstract : AIM–To evaluate the association between the immediate response to surfactant treatment and morbidity and mortality in infants with severe respiratory distress syndrome. METHODS–The response to surfactant was defined as the difference in the arterial:alveolar (delta a:A) ratio before and one hour after the first surfactant dose. Measurements were obtained from 253 Israeli infants participating in the multi-centre Curosurf 4 trial of surfactant replacement therapy. RESULTS–Delta a:A ratios ranged from -0.115 to 0.8 and were significantly related to both birth weight and gestational age. Among infants weighing 1001-1500 g mortality decreased from 40% among very bad responders to zero among good responders. The incidence of pneumothorax decreased with better response. Logistic regression analysis showed a hierarchy of predictive power for mortality: birth weight or gestational age; immediate response to surfactant; severity of initial disease. CONCLUSION–The immediate response to surfactant treatment is a significant prognostic indicator for mortality and morbidity.